Positioning “Techno-Economics”as an Interdisciplinary Reference Frame for Research and Teaching atthe Interface of Applied Natural Sciences and Applied Social Sciences: An Approach Based on Austrian IEM Study Programmes - Markus Zunk, Bernd (International Journal of Industrial Engineering and Management, 2018)
Students who want to address the “Techno-Economics”(TE) scientific community in their final assignment (i.e. master, diploma or doctoral thesis) are confronted with the specific challenges that interdisciplinary research poses. Hence, to help them respond to these challenges, this paper aims to draft a reference frame that provides orientation in this interdisciplinary research and teaching setting at the interface of “applied natural sciences”(in terms of engineering science resp. technology) and “applied social sciences”(in terms of business economics), without limiting freedom of thought within the research process. The presented TE teaching and research reference frame is primarily based on the needs of Austrian students of industrial engineering and management (IEM). It intends to enable both IEM students and researchers, first, to identify the relevant TE scientific community and, second, to become active within this scientific community with an adequate line of research. Article history: Received (12.09.2017);Revised (24.11.2017);Accepted (16.01.2018)